Effects of canagliflozin on cardiovascular death and hospitalization for heart failure by baseline estimated glomerular filtration rate: integrated analyses from the CANVAS Program and CREDENCE. (25th November 2020) - Mahaffey, K.W; Bakris, G; Blais, J; Cannon, C.P; Cherney, D; Damaraju, C.V; Gogate, J; Greene, T; Heerspink, H.J.L; Januzzi Jr, J.L; Kosiborod, M; Levin, A; et al.
Abstract: Background: People with type 2 diabetes mellitus (T2DM) have a greater risk of cardiovascular (CV) disease, including hospitalization for heart failure (HHF), a complication that is more common as renal function declines. The sodium glucose co-transporter 2 (SGLT2) inhibitor canagliflozin (CANA) reduced the risk of HHF in patients with T2DM and high CV risk or nephropathy in the CANVAS Program and CREDENCE trials, respectively. Methods: This post hoc analysis included integrated, pooled data from the CANVAS Program and the CREDENCE trial. The effects of CANA compared with placebo on CV death or HHF, HHF, and CV death were assessed in subgroups defined by baseline eGFR (<45, 45–60, and >60 mL/min/1.73 m 2 ). Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression models, with subgroup by treatment interaction terms added to test for heterogeneity. Interaction P values were calculated by including treatment group and baseline eGFR in the model. Results: A total of 14, 543 participants from the CANVAS Program (N=10, 142) and CREDENCE (N=4, 401) were included, with mean age, 65 y; 65% male; 75% white; mean eGFR 70.3 mL/min/1.73 m 2 . 1919 (13.2%) participants had baseline eGFR <45 mL/min/1.73 m 2 (mean, 36.7 mL/min/1.73 m 2 ), 2972 (20.4%) participants had eGFR 45–60 mL/min/1.73 m 2 (mean, 53.1 mL/min/1.73 m 2 ), and 9649 (66.3%) participants had eGFR >60 mL/min/1.73 m 2 (mean, 82.3 mL/min/1.73 m 2 ). Rates of CV death or HHF, HHF, and CV death increased as eGFR declined (Figure). CANA significantly reduced the risk of CV death or HHF and HHF compared with PBO, with consistent effects observed across subgroups. Conclusions: CV death or HHF, HHF, and CV death event rates increased with lower baseline eGFR. CANA significantly reduced the risk of CV death or HHF, jointly and individually, in participants with T2DM and high CV risk or CKD in the CANVAS Program and the CREDENCE trial, with consistent benefits observed regardless of baseline eGFR. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Janssen Scientific Affairs, LLC